2009
DOI: 10.1002/jrs.2375
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of vibrational spectra of copper phthalocyanine: polarized single‐crystal Raman spectra, isotope effect and DFT calculations

Abstract: The IR-and Raman spectra of copper phthalocyanine (CuPc), as well as the isotopic wavenumber shifts upon 15 N substitution in CuPc, were investigated experimentally and theoretically. The symmetry of molecular vibrations was determined using polarized Raman spectra of an oriented CuPc single crystal. Density functional theory (DFT) calculations were used for the detailed assignment of different bands in the vibrational spectra of CuPc. Theoretically predicted geometry, wavenumbers and isotopic shifts are in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 50 publications
7
86
0
Order By: Relevance
“…Moreover, Raman peaks in the high-wavenumber region are also strongly related to the intermolecular vibration [24]. The vibrational modes of a CuPc molecule can be found in [23,24,26], in which the A 1g , B 1g , and B 2g are defined as in-plane vibrations and E g an out-of-plane vibration mode. The Raman spectra of a CuPc crystal annealed at different temperatures are presented in Figure 6a with the wavenumbers ranging from 100 to 1600 cm −1 .…”
Section: Vibrational and Optical Properties Of Cupc Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Raman peaks in the high-wavenumber region are also strongly related to the intermolecular vibration [24]. The vibrational modes of a CuPc molecule can be found in [23,24,26], in which the A 1g , B 1g , and B 2g are defined as in-plane vibrations and E g an out-of-plane vibration mode. The Raman spectra of a CuPc crystal annealed at different temperatures are presented in Figure 6a with the wavenumbers ranging from 100 to 1600 cm −1 .…”
Section: Vibrational and Optical Properties Of Cupc Crystalsmentioning
confidence: 99%
“…FTIR and Raman spectra of CuPc have been extensively explored to determine the orientation of thin films and the polymorphic transitions [22][23][24]. UV-VIS spectrum has been proved to be suitable to study the crystal structures of CuPc, especially as shown in the recent report of Microscopic UV-VIS absorption measurements [25].…”
Section: Vibrational and Optical Properties Of Cupc Crystalsmentioning
confidence: 99%
“…In order to observe different behaviors in the terahertz band breathing mode of CuPc nano column under different growth time, low frequency Raman spectra were recorded and shown in Figure 4(b). Here three dominating vibrational peaks can be observed for growth time more than 10 min: Around 173 cm -1 (Peak 1), 234 cm -1 (Peak 2) and 257 cm -1 (Peak 3) are the in-plane vibration of isoindole, Cu-N stretching vibration and isoindole ring breathing mode, 16,22 respectively. The full width at half maximum (FWHM) of 173 cm -1 , 234 cm -1 and 257 cm -1 Raman modes were determined using the Gauss-Lorentz line shape fitting, which versus growth time of CuPc nano column grown on quartz were plotted as shown in Figure 4(c), respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The Raman spectra were analyzed in the 200-1800 cm -1 region. The bands assignment of the samples is based on general Raman data [18][19][20] , for dyes [19][20][21][22][23][24][25] and pigments [21][22][23][24][25][26] . The spectra are shown as obtained and are illustrated along with the discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Other bands in the spectrum mainly those at 1546, 742 and 687 cm -1 are consistent with the presence of CuPc. The bands assignment is displayed in Table 2 and it is based on published Raman data [18][19][20][21][22][23][24][25][26] . According to the molecular structure of CuPc and acetoacetic arylide, various functional chemical groups can be distinguishing.…”
mentioning
confidence: 99%